I’m an outlier! Is this important? – Answers based on a satisfaction and perception questionnaire - Leão, Celina Pinto (2017)
The objective of this work is to perceive the importance of an outlier behaviour in engineer students’ perception during the university course regarding: Teacher Involvement Perception, Student Interest, Student-Teacher interaction, Course organization and functioning Infrastructures, and Overall Satisfaction. The study was performed based on a questionnaire. A discussion on the presence of outliers for each of the items is also presented. Questions like: Are outliers important? Similar behaviour is founded independently of the student academic year?, and others, will be investigated and answered.